Analisis Kebutuhan Pemanfaatan Multimedia Interaktif di Era Digital Pada Siswa Kelas V SD - Febyarni, Febyarni Resvatina; Sumantri , Mohamad Syarif; Amri, Mira Amelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital age presents a dual challenge for elementary education: an abundance of information access coupled with a high risk of digital distraction. This study aims to conduct a needs analysis on the use of interactive multimedia for fifth-grade elementary school students as an effort to mitigate cognitive barriers. The research method used was quantitative descriptive, involving 26 fifth-grade students from SDN Pondok Kelapa 05 PG as research subjects. The data collection instrument consisted of a needs analysis questionnaire covering aspects of information literacy, cognitive load, and learning media preferences. The research results revealed the empirical fact that 86.5% of students experienced significant digital distraction when using devices for learning, and 88.5% of students felt bored with conventional learning media dominated by long texts. Consequently, 86.5% of students experienced difficulty formulating solutions to problems independently. A crucial finding indicates that 98.1% of students absolutely require interactive multimedia capable of serving as a focus guide (scaffolding). The conclusion of this study is that the development of interactive multimedia based on the Problem-Based Learning (PBL) model is an urgent need to manage students’ cognitive load and achieve digital literacy learning outcomes in elementary schools.